A New Method of Designing Circularly Symmetric Shaped Dual Reflector Antennas Using Distorted Conics. (16th December 2014) - Zaman, Mohammad Asif; Matin, Md. Abdul
Abstract : A new method of designing circularly symmetric shaped dual reflector antennas using distorted conics is presented. The surface of the shaped subreflector is expressed using a new set of equations employing differential geometry. The proposed equations require only a small number of parameters to accurately describe practical shaped subreflector surfaces. A geometrical optics (GO) based method is used to synthesize the shaped main reflector surface corresponding to the shaped subreflector. Using the proposed method, a shaped Cassegrain dual reflector system is designed. The field scattered from the subreflector is calculated using uniform geometrical theory of diffraction (UTD). Finally, a numerical example is provided showing how a shaped subreflector produces more uniform illumination over the main reflector aperture compared to an unshaped subreflector.